Study of antibiotic resistance gene transfer between isolates from patients with urinary tract infection via conjugation - Tabassum, Syeda Naushin (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of B.Sc in Microbiology, 2018.